2015
DOI: 10.1088/0004-637x/812/2/130
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Emissivity of Old Stellar Populations: A Local Group Census

Abstract: We study the unresolved X-ray emission in three Local Group dwarf elliptical galaxies (NGC 147, NGC 185 and NGC 205) using XMM-Newton observations, which most likely originates from a collection of weak X-ray sources, mainly cataclysmic variables and coronally active binaries. Precise knowledge of this stellar X-ray emission is crucial not only for understanding the relevant stellar astrophysics but also for disentangling and quantifying the thermal emission from diffuse hot gas in nearby galaxies. We find t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 58 publications
2
53
0
Order By: Relevance
“…A direct consequence of the MLT++ treatment of convection is that the effective temperature becomes higher, as illustrated by the above figure. panding 4 whereas stars with radiative envelopes respond by adiabatically contracting. For that reason, mass transfer from stars with outer convective envelopes is more likely to become dynamically unstable, possibly leading to a CE evolution (Webbink 1984;Hjellming & Webbink 1987;Ivanova et al 2013;Ge et al 2015;Pavlovskii & Ivanova 2015). To take this into account, population synthesis codes need to assume different stability criteria depending on whether the donor has a radiative or convective envelope.…”
Section: Model Variationsmentioning
confidence: 99%
“…A direct consequence of the MLT++ treatment of convection is that the effective temperature becomes higher, as illustrated by the above figure. panding 4 whereas stars with radiative envelopes respond by adiabatically contracting. For that reason, mass transfer from stars with outer convective envelopes is more likely to become dynamically unstable, possibly leading to a CE evolution (Webbink 1984;Hjellming & Webbink 1987;Ivanova et al 2013;Ge et al 2015;Pavlovskii & Ivanova 2015). To take this into account, population synthesis codes need to assume different stability criteria depending on whether the donor has a radiative or convective envelope.…”
Section: Model Variationsmentioning
confidence: 99%
“…Interestingly, in a broader comparison of X-ray emissivities of old stellar populations, Ge et al (2015) found that old open clusters not only have higher X-ray emissivities than globular clusters, but also than other old stellar populations without recent star formation, such as dwarf ellipticals, the outer bulge of M 31, and the solar neighbourhood. In those environments, the stellar density is much lower than in the cores of massive globular clusters, casting doubt on whether differences in density are solely responsible for the difference in X-ray output of old stellar populations.…”
Section: Comparison With Other Old Stellar Populationsmentioning
confidence: 99%
“…A key point of this paper is to address this question observationally, by considering the X-ray luminosity per unit mass in a range of environments of different stellar densities. We take advantage of a series of studies establishing the X-ray emissivity of a variety of old stellar populations (Sazonov et al 2006;Revnivtsev et al 2007Revnivtsev et al , 2008Warwick 2014;Ge et al 2015).…”
mentioning
confidence: 99%